The Role of International Business in Aid for Trade : Building Capacity for Trade in Developing Countries - World Bank (Washington, DC, 2014)
Since the launch of the global initiative on aid for trade in 2005, there has been a concerted effort by donors, partner agencies, and recipients to strengthen trade capacity and improve trade-related infrastructure so that developing countries may reap the benefits of trade. The majority of these efforts have been driven by the public sector: building infrastructure, providing technical assistance, improving trade facilitation, and trade policies. With a growing number of companies looking to the developing world for new markets, the private sector has a profound interest in ensuring sound investments through access to trade-related infrastructure, an educated workforce, and quality standards for inputs to their goods. The time is ripe to explore new partnerships between the public and private sector in order to build trade capacity in developing countries. This paper is a step towards highlighting the role of the private sector in the aid for trade initiative and provides a framework for understanding what this role entails. This framework is informed by 40 case stories submitted by multinational companies, business associations, and other private sector actors, which cover a variety of trade related capacity building projects. These case stories demonstrate the importance of the private sector in building human and productive capacity, incorporating producers into global value chains, improving quality and safety standards, and promoting trade facilitation. The paper concludes by highlighting seven ways in which the private sector engages with the aid for trade initiative and provides several avenues for bolstering future collaboration between the public and private spheres.